Ultra-fast etching of photoresist by reactive atmospheric-pressure thermal plasma jet with surface temperature measurement - Kyohei Matsumoto; Hibiki Kato; Jiawen Yu; Hiroaki Hanafusa; Seiichiro Higashi (Applied Physics Express)
Atmospheric-pressure reactive thermal plasma jet (R-TPJ) with Ar and O _2 gas mixture was applied to the etching of photoresist (PR) on a silicon wafer. Optical interference contactless thermometry (OICT) and optical emission spectroscopy were carried out to clarify the relationship between the etching rate, amount of atomic oxygen radicals, and PR surface temperature. The results show that the O _2 flow rate and surface temperature are obviously related to the etching rate of the PR. The R-TPJ irradiation with input current at 60 A reaches surface temperature of 720 K within 7 ms and achieved an etching rate of 84 μ m s ^−1 .